Value of Serum IgG4 in the Diagnosis of Autoimmune Pancreatitis and in Distinguishing it from Acute and Chronic Pancreatitis of Other Etiology - Zhu, MD, PhD, Xiaoqin; Al-Turkmani, PhD, M. Rabie; Rao, PhD, Lokinendi V. (North American Journal of Medicine and Science, 2017)
Immunoglobulin G4 (IgG4)-related autoimmune pancreatitis (AIP) is one of the most common clinical presentations of the IgG4-related disease and distinct from acute pancreatitis and chronic pancreatitis derived from other etiology. Elevated serum IgG4 concentration has been established as one of the diagnostic criteria for AIP. However, a subset of patients of AIP have normal serum IgG4. It is essential to establish the value of serum IgG4 level in identifying AIP patients in clinical setting, and its association with the severity of the disease and the pathology diagnosis. We performed a retrospective study involving 67 patients who were identified to have elevated serum IgG4 measurements (>86 mg/dL) from a pool of 833 patients in our institute from 2012 to 2015. The concentration of serum IgG4 was significantly higher in AIP compared to acute pancreatitis and chronic pancreatitis of other etiology (p<0.01). The sensitivity of distinguishing AIP from acute and chronic pancreatitis of other etiology increased from 61% to 100% as the cutoff value for serum IgG4 was set from 135 mg/dL to 86 mg/dL. On the other hand, the specificity was decreased from 98% to 91%. A cutoff value of 120 mg/dL gave rise to the highest specificity without sacrificing the sensitivity. The level of serum IgG4 exhibited a trend to associate with the severity of IgG4-related AIP determined clinically based on the endoscopic ultrasound findings, although it did not reach statistical significance (p value = 0.05). All the pathology-proven cases of IgG4-related AIP exhibited elevated serum IgG4 concentration. Only one of eight cases of non-AIP cases confirmed by pathology showed elevated serum IgG4. [N A J Med Sci. 2017;10(3):94-99. DOI: 10.7156/najms.2017.1003094]